Nanoproteomic analysis of extracellular receptor kinase‐1/2 post‐translational activation in microdissected human hyperplastic colon lesions. Issue 9 (4th April 2013) - Drew, David A.; Devers, Thomas; Horelik, Nicole; Yang, Shi; O'Brien, Michael; Wu, Rong; Rosenberg, Daniel W.
<x xml:space="preserve">Abstract</x> Oncogenic activation resulting in hyperproliferative lesions within the colonic mucosa has been identified in putative precancerous lesions, aberrant crypt foci (ACF). KRAS and BRAF mutation status was determined in 172 ACF identified in the colorectum of screening subjects by in situ high‐definition, magnifying chromoendoscopy. Lesions were stratified according to histology (serrated vs. distended). Due to their limiting size, however, it was not technically feasible to examine downstream signaling consequences of these oncogenic mutations. We have combined ultraviolet‐infrared (UV/IR) microdissection with an ultrasensitive nanofluidic proteomic immunoassay (NIA) to enable accurate quantification of posttranslational modifications to mitogen‐activated protein kinase (MAPK) in total protein lysates isolated from hyperproliferative crypts and adjacent normal mucosa. Using this approach, levels of singly and dually (activated) phosphorylated isoforms of extracellular receptor kinase(ERK)‐1 and ERK‐2 were quantified in samples containing as little as 16 ng of total protein recovered from <200 cells. ERK activation is responsible for observed hyperplasia found in these early lesions, but is not directly dependent on KRAS and/or BRAF mutation status. This study describes the novel use of a sensitive nanofluidic platform to measure oncogene‐driven proteomic changes in diminutive lesions and highlights the advantage of this approach over classical immunohistochemistry‐based analyses.